Penerapan Langgam Arsitektur Fungsionalisme pada Bangunan TWA Flight Center - Celine Andriani; Josephine Roosandriantini (Tekstur (Jurnal Arsitektur), 2022)
Architecture is the art of designing a building and modern architecture is one of the various architectural concepts. This architectural style eliminates ornaments and prioritizes the function of a building. In modern architecture, there are various styles, namely Art Nouveau, Expressionism, International Style, Functionalism, Cubism, Organic Architecture, De Stijl, futuristic, and Brutalism. One example of a modern architectural building is the TWA Flight Center, which is located in New York City and the building has a free form. The purpose of writing this journal is to find out about the architectural style of TWA Flight Center using quantitative descriptive methods to prove that TWA Flight Center uses the architectural style of functionalism